Omission of aspirin in patients taking oral anticoagulation after percutaneous coronary intervention: a systematic review and meta-analysis. Issue 2 (March 2019) - Zhang, Jian; Wang, Zheng; Sang, Wentao; Wei, Maozeng; Xu, Feng; Chen, Yuguo
Abstract : Background: There is no consensus on optimal antiplatelet and anticoagulation therapy after coronary stenting. Methods: We identified randomized controlled trials (RCTs) published in PubMed, Cochrane Library, and Embase using the following keywords: 'antiplatelet', 'dual therapy', 'triple therapy', 'antithrombosis', 'indication for anticoagulation', 'percutaneous coronary intervention', and 'RCTs'. Primary safety end points were relative bleeding events, and secondary efficacy end points were major adverse cardiovascular events including stent thrombosis, death, myocardial infarction, and stroke. Results: We identified three RCTs including 5387 patients, of whom 2719 (50.5%) received dual therapy (DT) and 2668 (49.5%) received triple therapy. Relative to triple therapy, DT was associated with lower Thrombolysis in Myocardial Infarction major bleeding [risk ratio (RR): 0.58; 95% confidence interval (CI): 0.42–0.82], Thrombolysis in Myocardial Infarction minor bleeding (RR: 0.46; 95% CI: 0.34–0.62), and clinical bleeding events (RR: 0.61; 95% CI: 0.47–0.81). There was no significant difference for the secondary efficacy end point. In subgroup analyses, results were similar by sex, bleeding risk, and stent type; however, DT appeared suitable for patients aged less than 75 years but not more than or equal to 75 years, implying that there may be no ideal therapy for patients older than 75 years to balance the risk of ischemia and bleeding at the same time. Conclusion: Among patients with an indication for oral anticoagulation after percutaneous coronary intervention, DT appears to be the optimal strategy. Abstract : Supplemental Digital Content is available in the text.